Implementasi Kepemimpinan Transformasional Fauziah Fauzan El-Muhammady di Perguruan Diniyyah Puteri Padang Panjang - Hamid, Abdul Waris; Santosa, Sedya (ISLAMIKA, 2024)
This study aims to describe how the implementation of Fauziah Fauzan El-Muhammady's leadership. This research was conducted at the Diniyyah Puteri College, Padang Panjang, West Sumatra. This research is a field research using a qualitative descriptive method. The data analysis technique is using analysis techniques according to Miles and Huberman, namely data reduction, data display, and data verification. The results of the study explain how Fauziah Fauzan's style of transformational leadership is by giving idealistic influence to all members of the Diniyyah Puteri college, providing inspiration, and intellectual stimulation, giving individual considerations, emphasizing the direction to be aimed by school principals at various levels of education units through vision statements, and a clear mission.